The use of innovative approaches to strengthen health system resilience during the COVID-19 pandemic: case studies from selected Commonwealth countries - Mghamba, Janneth; Gilmour, Emily; Robinson, Layne; Simba, Azma; Tuyishime, Albert; Persaud, Anand; Mwansambo, Charles; Somatunga, Lakshmi; Werema, Solomon; Mchwampaka, Witness; Makundi, Vida; Remedius, Kakulu; et al. (Frontiers in Public Health, 2023)
This article is part of the Research Topic ‘Health Systems Recovery in the Context of COVID-19 and Protracted Conflict’. The COVID-19 pandemic has exposed the vulnerabilities and limitations of many health systems and underscored the need for strengthening health system resilience to make and sustain progress toward Universal Health Coverage (UHC), global health security and healthier populations in tandem. In response to the COVID-19 pandemic, Commonwealth countries have been practicing a combination of innovative integrated approaches and actions to build health systems resilience. This includes utilizing digital tools, improvements in all-hazard emergency risk management, developing multisectoral partnerships, strengthening surveillance and community engagement. These interventions have been instrumental in strengthening national COVID-19 responses and can contribute to the evidence-base for increasing country investment into health systems resilience, particularly as we look toward COVID-19 recovery. This paper gives perspectives of five Commonwealth countries and their overall responses to the pandemic, highlighting practical firsthand experiences in the field. The countries included in this paper are Guyana, Malawi, Rwanda, Sri Lanka, and Tanzania. Given the diversity within the Commonwealth both in terms of geographical location and state of development, this publication can serve as a useful reference for countries as they prepare their health systems to better absorb the shocks that may emerge in future emergencies.